Narrators, Narratees, and Narratives in Ancient Greek Literature Studies in Ancient Greek Narrative, Volume One - Nünlist, René; Bowie, Angus M.; de Jong, Irene (Mnemosyne, Supplements, 2004)
This is the first part of a new narratological history of Greek literature, which deals with the definition and boundaries of narrative and the role of narrators and narratees.; Readership: All those interested in ancient Greek literature, narrative theory, literary history, comparative literature.